Illegitimate authorship and flawed procedures: Fundamental, formal criticisms of the Declaration of Helsinki. (5th September 2018) - Ehni, Hans‐Joerg; Wiesing, Urban
Abstract: Some of the recent criticisms published during and after the last revision process of the Declaration of Helsinki are directed at its basic legitimacy. In this article we want to have a closer look at the two criticisms we consider to be the most fundamental. The first criticism questions the legitimate authorship of the World Medical Association to publish a document such as the Declaration. The second fundamental criticism we want to examine argues that the last revision process failed to meet the standards for fair, democratic procedures. Although both criticisms deny the formal legitimacy of the Declaration in the most fundamental way, they have never been addressed in detail in a single article. We refute most of the related arguments. However, acknowledging some of the points made, improvements for future revision processes and versions of the Declaration of Helsinki are outlined.